ANALISIS EFEKTIVITAS BIAYA PENGGUNAAN ANTIBIOTIK SIPROFLOKSASIN DAN SEFTRIAKSON PADA PASIEN INFEKSI SALURAN KEMIH RAWAT INAP DI RSU ANUTAPURA PALU TAHUN 2016-2017 - Siti Atika; Ihwan Ihwan; Muhamad Rinaldhi Tandah (Fakultas Farmasi UMI, 2018)
Urinary tract infection is an infection that comes from bacteria and affects the top or bottom of the urinary tract. Effective treatment can be done by choosing and using appropriate antibiotics. The principle of selecting antibiotics is called cost effective. This study aims to analyze the cost-effectiveness of using ciprofloxacin and ceftriaxone antibiotics in patients with urinary tract infection. The method used is retrospectively quantitative. Data obtained from medical records, and medical payment in the form of direct medical costs of ciprofloxacin and ceftriaxone antibiotics on inpatient with urinary tract infection at General Hospital Anutapura in the period of 2016-2017. The results showed the cost-effectiveness of antibiotics ceftriaxone is more cost effective than ciprofloxacin antibiotics with an ACER value of Rp12.249,5 and ICER value of Rp2.336,5. Based on the cost-effectiveness of antibiotics the results of chi-square test obtained p value = 0.157, it is concluded that there is no significant difference between ciprofloxacin and ceftriaxone.